Cochlear Implantation in Neurological Patients: Case Report and Literature Survey. (27th April 2020) - Barbara, Maurizio; Margani, Valerio; Costanzo, Rocco; Salvetti, Marco; Bozzao, Alessandro; Monini, Simonetta; Covelli, Edoardo
Abstract : Cochlear implant (CI) is a reliable solution to restore hearing in people with severe‐to‐profound hearing loss. The device is made up of internal and external components linked transcutaneously through a magnet that may rise specific issues in people who must undergo brain magnetic resonance (MRI) due to neurological diseases. The description of a case of a CI implantee needing MRI has given us the opportunity to highlight the differences that can be encountered among different neuropathies, either acute or chronic, with the aim of shedding some light for finding a common protocol when facing this important and frequent clinical issue. In particular, the removal of the magnet prior to performing an MRI exam is mandatory for brain diseases ipsilateral to the implanted side, whereas for contralateral side lesions it is less important when using apposite bandage kits. Laryngoscope, 131:E576–E580, 2021